THE INFLUENCE OF DIVIDEND POLICY, PROFITABILITY, AND CORPORATE GOVERNANCE (CG) ON COMPANY VALUE (EMPIRICAL STUDY ON GO PUBLIC COMPANIES LISTED IN CGPI INDEX IMPROVEMENTS 2010-2017) - Wahyu Widiastuti; Tri Gunarsih (MESP–FEB UNS, 2019)
This study aims to analyse the effect of the proxy policy dividend with Dividend Payout Ratio on firm value, the effect of proxied profitability with Return On Equity on firm value, and the effect of Corporate Governance proxied by the CGPI index on firm value. The company's value in this study is proxy by Price to Book Value. The independent variables in this study are dividend policy, profitability, and corporate governance, while company value is the dependent variable. This research is a type of quantitative research. The sample of companies in this study were 15 companies that go public on the Indonesia Stock Exchange (IDX) listed on The Indonesian Institute for Corporate Governance (IICG) and received a rating of the CGPI index (Corporate Governance Perception Index) in 2010 to 2017. So the amount of data in this study are 120 data. Sampling in this study uses a purposive sampling method that uses several terms and criteria. Data analysis in this study used descriptive statistical tests, multiple linear regression tests, and the classic assumption test consisting of normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests. While the statistical tests in this study use the coefficient of determination (R²) test, srimultan test (F test), partial test (t test). Based on the results of research that has been done, it shows that the dividend policy which is proxied by the Dividend Payout Ratio has no effect on the value of the company, Profitability which is proxied by Return On Equity has a positive and significant effect on company value, and Corporate Governance using the CGPI index has a positive and significant effect to the value of the company. Keywords: Company Value, Dividend Policy, Profitability, Corporate Governance (CG)